THE The Impact Of Parental Involvement On The Academic Performance Of Primary Education Of Children In CBSE Schools In Dubai - Aysha Siddekha Khaleel; Lubna Ali Mohammed (Journal Research of Social Science, Economics, and Management, 2023)
ABSTRACT This study aims to investigate the connection between parental support and academic achievement among primary school students (grades 1 to 5) in CBSE (Central Board of Secondary Education) schools. CBSE schools are known for their precise academic standards, and their primary education curriculum highlights physical, emotional, social, and mental development, requiring support from parents. This research focuses on both working and single stay-at-home parents and their impact on academic performance based on the amount of time they offer to their children's academics daily. The research question is whether there is a connection between parental support and academic achievement, considering the conditions of both working and stay-at-home parents. As students spend more time with their families than at school, it is expected that their academic performance will be affected by their family environment. Therefore, this study seeks to investigate the relationship between parental involvement in school and students' academic achievement. The research will involve a general study of both working and stay-at-home parents and their levels of parental support for academics. A quantitative research approach will be used, with 140 parents of primary school students (both working and single stay-at-home) completing a Microsoft form questionnaire to evaluate their parental support and its impact on academic performance.